New Insights on Psychological Factors for the Development of Women Entrepreneurs in Indonesia. Issue 2 (May 2020) - Riantoputra, Corina D.; Muis, Ismarli
The Problem: Despite efforts to develop women entrepreneurs in Indonesia, the majority of them are unable to grow their businesses. The literature suggests that cultural factors (i.e., non-egalitarian sex roles) may limit the actualization of psychological factors that are critical for their successes. The Solution: To investigate the motivation, challenges, and opportunities facing women entrepreneurs in Indonesia, this article focused on (a) characteristics of women entrepreneurs based on their motives: necessity- versus growth-oriented, and (b) psychological factors that influence their success. Focusing on micro and small enterprises, we collected data from 200 (87 necessity-oriented, and 113 growth-oriented) women entrepreneurs in Indonesia. The study findings demonstrate that the success of women entrepreneurs in Indonesia is associated with their identity conflict (i.e., induced by non-egalitarian sex-role culture), passion, and future time orientation, all of which interplay differently for necessity- and growth-oriented women entrepreneurs. The Stakeholders: This article is important for scholars, practitioners, and government officers in a non-egalitarian sex-role country like Indonesia. It informs involved stakeholders of the specific aspects that need to be considered in coaching and leadership training for women entrepreneurs who are managing micro and small enterprises.